ANALISIS PERTIMBANGAN HAKIM MENGENAI “ALASAN MENDESAK” DALAM SE MENAKERTRANS NO. SE-13/MEN/SJ/HK/I/2005 (STUDI KASUS PUTUSAN NOMOR 139PK/PDT.SUS-PHI/2016) - Anastasia Prestika; Andari Yurikosari (Jurnal Hukum Adigama, 2020)
In the Civil Code governing the Agreement in Book III, one of which is an agreement governing employment or what is known as an Employment Agreement (Article 1601 Civil Code) and further stipulated in Law Number 13 of 2003 concerning Employment (Labor Law). In work relations, disputes often arise between employers and workers, there are 4 types of disputes, namely rights disputes, disputes of interest, disputes of termination of employment and disputes between workers in one company. Disputes that most often occur are disputes about termination of employment because workers have made a grave mistake as stipulated in Article 158 Paragraph (1) of the Labor Law. Regarding termination of employment due to the mistakes of workers / laborers feeling there is injustice, a judicial review is submitted to the Constitutional Court, with decisions regarding these articles which do not have binding legal force. Then it was followed up by the Minister of Manpower and Transmigration by issuing Circular Letter Number: SE.13 / MEN / SJ-HK / I / 2005, that layoffs can be fixed after receiving a criminal court decision that is still legal force and if there is an "urgent reason" then it can directly apply to the settlement institution of industrial relations disputes.